The Influence of Islamic Religious Education Based on Religious Moderation and National Defence on The Nationalism of Students - Solechan, Achmad; Zuhdi, Muhammad Luthfi; Syauqillah, Muhammad (Journal of Ecohumanism, 2024)
Realizing the rise in cases of intolerance in the academic world, various approaches to handling intolerant-violent and radical acts in the name of Islam are always being pursued. One of these approaches is a deradicalization program through religious moderation education in Islamic Religious Education. One of the deradicalization programs through religious moderation education in Islamic Religious Education is implemented by the University of Indonesia (UI). The University of Indonesia (UI) has made learning Islamic Religious Education based on religious moderation a mandatory subject for new UI Muslim students in the first semester and includes Islamic Religious Education based on religious moderation in the Personality Development Course (MPK) group. By using descriptive research methods with a quantitative approach, the author found that the data analysis that the author carried out showed that rcount 0.58 > rtable 0.1966 with an error level of 0.05 and a total of N=100. Interpretation of the level of relationship to the correlation coefficient of these two variables shows that there is a significant influence from learning Islamic Religious Education based on religious moderation and national defense on the nationalism of Indonesian university students in 2022.